Reformasi Pendidikan sebagai Tuntutan Sejarah - Nawawi Nawawi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
The system of national education considered necessary a reform. During the time national education only yielding depressed human being, is not critical and is not creative, thinking and acting only according to power structure. National education have to be returned to powered of society and to realize the new vision of society Indonesia which Madani. National education represent the demand foundament commended by constitution 1945. Therefore national education have to as according to constitution, realizing democratic society, esteem the human right and form of government smart Indonesian nation.